Precision measurement of the Λ0b baryon lifetime - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
The ratio of the Λ0b baryon lifetime to that of the B̄0 meson is measured using 1.0 fb−1 of integrated luminosity in 7 TeV center-of-mass energy pp collisions at the LHC. The Λ0b baryon is observed for the first time in the decay mode Λ0b→J/ψpK−, while the B̄0 meson decay used is the well known B̄0→J/ψπ+K− mode, where the π+K− mass is consistent with that of the K̄*0(892) meson. The ratio of lifetimes is measured to be 0.976±0.012±0.006, in agreement with theoretical expectations based on the heavy quark expansion. Using previous determinations of the B̄0 meson lifetime, the Λ0b lifetime is found to be 1.482±0.018±0.012 ps. In both cases, the first uncertainty is statistical and the second systematic.
Im Titel ist "0" hochgestellt und "b" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 617
Gesehen am 22.04.2021